PENGARUH METACOGNITIVE AWARENESS DAN SOSIAL MEDIA ADDICTION TERHADAP PROKRASTINASI AKADEMIK PADA SISWA KOMPETENSI KEAHLIAN AKUNTANSI SMK NEGERI DI JAKARTA PUSAT - Risma Nabila; Dwi Kismayanti Respati; Khansha Sindra Irfani (STKIP Subang, 2026)
This study aimed to examine the effects of metacognitive awareness and social media addiction on academic procrastination among Accounting students at public vocational high schools (SMK Negeri) in Central Jakarta. This study employed a survey method with a quantitative approach. The accessible population consisted of 178 eleventh-grade students majoring in Accounting at SMKN 2 Jakarta, SMKN 14 Jakarta, and SMKN 16 Jakarta, with a sample of 124 students. Data were collected using a questionnaire. The data were analyzed using descriptive statistics, normality tests, linearity tests, multiple linear regression analysis, coefficient of determination analysis, F-test, and t-test with the assistance of SPSS software. The results indicated that metacognitive awareness had a negative effect on academic procrastination. This was evidenced by a significance value of 0.000 < 0.05 and a regression coefficient of -0.343. Meanwhile, social media addiction had a positive effect on academic procrastination, as indicated by a significance value of 0.000 < 0.05 and a regression coefficient of 0.447. Furthermore, metacognitive awareness and social media addiction simultaneously had a significant effect on academic procrastination.